Preparation of Fucoxanthin-Loaded Nanoparticles Composed of Casein and Chitosan with Improved Fucoxanthin Bioavailability - Koo, Song Yi; Mok, Il-Kyoon; Pan, Cheol-Ho; Kim, Sang Min (AMER CHEMICAL SOC, 2016)
To facilitate the utilization of fucoxanthin (FX), a valuable marine carotenoid, in the food industry, FX-loaded casein nanoparticles (FX-CN) and chitosan-coated FX-CN (FX-CS-CN) were developed using the FX-enriched fraction from Phaeodactylum tricornutum. Two nanoscale particles (237 +/- 13 nm for FX-CN and 277 +/- 26 nm for FX-CN-CN) with spherical and smooth surfaces showed over 71% encapsulation efficiency and polydispersity index (PDI) value of 0.31-0.39 in water. Owing to the chitosan coating, FX-CS-CN showed a positive zeta potential (24.00 mV), whereas that of FX-CN was negative (-12.87 mV). In vitro simulated digestion demonstrated better FX bioaccessibility from the nanoparticles versus P. tricornutum powder (Pt-powder) and from FX-CN versus FX-CS-CN. However, in C57BL/6 mice, fucoxanthinol absorption to the blood circulation was two times higher for FX-CS-CN versus FX-CN, possibly due to increased retention or adsorption to mucin by the cationic biopolymer in the chitosan-coated particles. These results demonstrate that FX-CS-CN can enable the application of FX, with improved bioavailability and water dispersibility, in the food industry.
Keywords: IN-VIVO PHARMACOKINETICS; SODIUM CASEINATE; DRUG-DELIVERY; STABILITY; VITRO; CURCUMIN; FORMULATION; NANOGELS; SYSTEMS; CARRIER